2020
DOI: 10.1371/journal.pbio.3000885
|View full text |Cite
|
Sign up to set email alerts
|

NOX5-induced uncoupling of endothelial NO synthase is a causal mechanism and theragnostic target of an age-related hypertension endotype

Abstract: Hypertension is the most important cause of death and disability in the elderly. In 9 out of 10 cases, the molecular cause, however, is unknown. One mechanistic hypothesis involves impaired endothelium-dependent vasodilation through reactive oxygen species (ROS) formation. Indeed, ROS forming NADPH oxidase (Nox) genes associate with hypertension, yet target validation has been negative. We re-investigate this association by molecular network analysis and identify NOX5, not present in rodents, as a sole neighbo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
31
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
4
2
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 33 publications
(31 citation statements)
references
References 116 publications
(148 reference statements)
0
31
0
Order By: Relevance
“…Therefore, NOX5 may participate in neuronal degeneration mediated by BBB alterations triggered via ROS accumulation that allow to postulate this oxidase as a therapeutic target in cerebral ischemic injury. In our study, these BBB alterations due to NOX5 may not be mediated by increased systolic blood pressure levels [ 38 ] but through other mechanisms, like COX2 activation. To analyze the BBB integrity, we evaluated the cerebral extravasation of fibrin and IgG, and we found a higher tendency of fibrin extravasation in the knock-in mice.…”
Section: Discussionmentioning
confidence: 91%
See 1 more Smart Citation
“…Therefore, NOX5 may participate in neuronal degeneration mediated by BBB alterations triggered via ROS accumulation that allow to postulate this oxidase as a therapeutic target in cerebral ischemic injury. In our study, these BBB alterations due to NOX5 may not be mediated by increased systolic blood pressure levels [ 38 ] but through other mechanisms, like COX2 activation. To analyze the BBB integrity, we evaluated the cerebral extravasation of fibrin and IgG, and we found a higher tendency of fibrin extravasation in the knock-in mice.…”
Section: Discussionmentioning
confidence: 91%
“…Moreover, NOX5 is known to potentiate cardiac remodeling and the dysfunction of hypertensive angiotensin II-induced mice expressing NOX5 in the heart under the α-myosin heavy-chain promoter [ 37 ]. Additionally, in another knock-in mouse, which expressed NOX5 under the Tie2 promoter specific to the endothelium and white blood cells, the authors found that chronic NOX5 expression induced elevated systolic blood pressure levels in aging mice [ 38 ]. In our study, no differences in the systolic blood pressure measurements in the aging mice were observed.…”
Section: Discussionmentioning
confidence: 99%
“…In large elastic conduit arteries, endothelial NOS produces NO that causes smooth muscle relaxation via production of cGMP. Superoxide anions produced by NADPH oxidases and mitochondria inhibit this pathway by uncoupling of eNOS, binding and inactivation of NO and damaging sGC (Daiber et al, 2017;Elbatreek et al, 2020;Evgenov, Pacher, Schmidt, Hasko, Schmidt & Stasch, 2006;Forstermann & Munzel, 2006;Monica, Bian & Murad, 2016;Zhang, Murugesan, Huang & Cai, 2020). In addition to NO, NOS can produce HNO and O 2 - (Forstermann & Munzel, 2006;Schmidt, Hofmann, Schindler, Shutenko, Cunningham & Feelisch, 1996).…”
Section: Discussionmentioning
confidence: 99%
“…Selection of novel circulating factors can be hypothesis-driven and lead to confirmatory studies in dedicated experimental animals. These approaches were recently applied with respect to the role of a subtype of NADPH oxidases (NOX5) in the development of regional endothelial dysfunction and systolic hypertension with ageing (Elbatreek et al, 2020).…”
Section: Discussionmentioning
confidence: 99%
“…A similar murine model, with increased expression of human Nox5 in the endothelium, has shown age-related severe systolic hypertension, and impaired endothelium-dependent vasodilation, as a result of Nox5-induced uncoupling of eNOS [ 156 ]. Further work within a conditional endothelial NOX5 knock-in mouse, has identified a role for Nox5 in the response to ischaemia as a result of myocardial infarction, with evidence that Nox5-derived ROS may modulate the COX-2 and PGE 2 axis in EC.…”
Section: Nox5 In Type 2 Diabetes Mellitus Related Endothelial Dysfunctionmentioning
confidence: 99%